2005
DOI: 10.1007/s10811-005-8700-8
|View full text |Cite
|
Sign up to set email alerts
|

Cyanobacterial blooms and water quality in Greek waterbodies

Abstract: The cyanobacterial species composition of nine Greek waterbodies of different type and trophic status was examined during the warm period of the year (May-October). Cyanobacterial water blooms were observed in all waterbodies. Forty-six cyanobacterial taxa were identified, 11 of which are known to be toxic. Eighteen species are reported for the first time in these waterbodies, 8 of which are known to produce toxins. Toxin producing species were found in all of the waterbodies and were primarily dominant in blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
1
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 31 publications
2
61
1
4
Order By: Relevance
“…3e). Petaloti et al (2004) Precipitation, Prec (mm y and was dominated by cyanobacteria (Snowella lacustris) (Cooke et al, 2005;Vardaka et al, 2005). More recently, Ioakimidou (2010) observed that cyanobacteria dominated the phytoplankton community of the lake, accounting for more than 86% of total abundance.…”
Section: Case Studiesmentioning
confidence: 99%
“…3e). Petaloti et al (2004) Precipitation, Prec (mm y and was dominated by cyanobacteria (Snowella lacustris) (Cooke et al, 2005;Vardaka et al, 2005). More recently, Ioakimidou (2010) observed that cyanobacteria dominated the phytoplankton community of the lake, accounting for more than 86% of total abundance.…”
Section: Case Studiesmentioning
confidence: 99%
“…Sphaerocystis schroeteri and Microcystis aeruginosa performed the second peak in early autumn. The summer and autumn growth of Microcystis aeruginosa in eutrophic and hypertrophic lakes was reported to be characteristic by many authors (Naselli-Flores and Barone, 2000; Vardaka et al, 2005).…”
Section: Phytoplankton Composition and Seasonal Variationsmentioning
confidence: 81%
“…In Greece, common bloom-forming cyanobacteria mainly belong to the genera Microcystis and Anabaena, followed by Cylindrospermopsis and Aphanizomenon [1,4,5]. In addition to the bloom-forming cyanobacteria, a wide range of less abundant and lesser-known cyanobacteria, such as, filamentous (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Pseudanabaena) or colonial (e.g. Aphanocapsa, Chroococcus, Cyanodictyon) nanoplanktonic (2-20 μm) species [4] and Synechococcustype picocyanobacteria (<2 μm) [6] are present in blooms that rarely become dominant, but can represent an important part of the total cyanobacterial biomass. Occasionally, benthic and/or periphytic cyanobacteria can be observed in phytoplankton.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation